Characterizing clinical outcomes and factors associated with conduction gaps in VISITAG SURPOINT‐guided catheter ablation for atrial fibrillation. Issue 3 (7th May 2021) - Inoue, Koichi; Tanaka, Nobuaki; Ikada, Yusuke; Mizutani, Akihiro; Yamamoto, Kazuhiko; Matsuhira, Hana; Harada, Shinichi; Okada, Masato; Iwakura, Katsuomi; Fujii, Kenshi
Abstract: Purpose: Although usefulness of VISITAG SURPOINT (VS) on pulmonary vein isolation (PVI) in catheter ablation of atrial fibrillation has been reported, optimal VS thresholds can depend on the inter‐tag distance (ITD) and vice versa. We validated the efficacy of PVI with lower target ITDs and VS values than in previous studies. Methods: Retrospective review of consecutive patients (N = 100) with paroxysmal (n = 32) or persistent AF (n = 68) undergoing VS‐guided ablation between 09/2018 and 08/2019 was conducted. All procedures were performed by two operators. Target VS values were 425 (anterior), 375 (posterior), and 325 (near the esophagus). Target ITD was 4 mm. Results: Acute PVI was achieved in all cases, however, 13 residual gaps in 12 patients were observed after initial encirclement (first pass isolation: 88%). Ten gaps due to spontaneous PV reconnections (PVR) were found in nine patients (9%). These 23 gaps had similar median VS (gap‐related vs non‐gap: 429 vs 410, P  = .4545) and power (36 vs 36W, P  = .4843), higher contact force (13.8 vs 11.0g, P  = .0061), and larger ITD (5.3 vs 3.7mm, P  < .001) when compared to the remaining tags. Only ITDs were independently associated with gap formation in multivariate analysis. One‐year Kaplan‐Meier freedom from any atrial arrhythmia was 87.2%. Eight patients received repeat ablation (8.1%) and of these, 6 (75%) were free from PVR. Conclusion: Favorable rates of first pass isolation, acute PVR, and long‐term procedure success were achieved using lower VS values than in previous reports. With a target VS value of 375‐425, ITDs of 4 mm was sufficient for durable PVI. Abstract : With a target VS value of 375‐425, ITDs of 4 mm was sufficient for durable PVI.